The Development of Interactive Learning Media Based on Discovery Learning Oriented to Students’ Concept Understanding and Mathematical Disposition - Tiara Saharani; Agus Maman Abadi (STAI Hubbulwathan Duri, 2024)
Interactive learning media that enhance active student participation are essential for optimizing mathematics learning and developing mathematical competencies. This research focused on designing interactive media based on discovery learning to improve students' conceptual understanding and mathematical disposition, ensuring their validity, practicality, and effectiveness. The study utilized the ADDIE development model, encompassing Analysis, Design, Development, Implementation, and Evaluation phases. The research involved 35 students from class XI SMA Negeri 4 Yogyakarta and assessed the media's validity, implementation practicality, and learning effectiveness. The interactive media were developed following discovery learning principles and made accessible via laptops and smartphones. Validation confirmed their effectiveness, achieving a 92.3% implementation rate. Wilcoxon and proportion tests revealed significant improvements in students' conceptual understanding and mathematical disposition. The average concept understanding test score exceeded the KKTP threshold (75), while the mathematical disposition questionnaire average surpassed the high criteria minimum (102). Furthermore, 88.5% of students reached the KKTP (75) threshold in conceptual understanding, and 94.2% met the high criteria (102) for mathematical disposition. The findings indicate that discovery learning-based interactive media significantly enhance students' conceptual understanding and disposition. The accessibility and engagement features align well with effective learning strategies for high school mathematics. Discovery learning-based interactive media are valid, practical, and effective tools for improving mathematical understanding and disposition in high school settings, supporting broader adoption in similar educational contexts.